Beasiswa Juare Sebagai Instrumen Soft Power Dalam Pembangunan Sumber Daya Manusia di Kota Cilegon - Anatul Widiyanti; Laeli Nur Khanifah; Astri Agustriani; Asti Julianidisi; Nathania Aulia Damayanti (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the Cilegon Juare Scholarship Program as an instrument of human resource development and local government soft power. Using a qualitative descriptive approach, data were collected through interviews, observation, documentation, and literature review. The findings show that the program contributes to expanding access to higher education, improving human resource quality, and strengthening the positive image and public trust toward the Cilegon City Government. However, several challenges remain, including limited quotas, beneficiary data accuracy, and delays in fund disbursement. Therefore, improvements in program management and implementation are needed to optimize its impact and sustainability.